Investigation of the biomechanical and histopathological effects of autologous conditioned serum on healing of Achilles tendon - Genc, Erdinc; Beytemur, Ozan; Yuksel, Serdar; Eren, Yilmaz; Caglar, Aysel; Kucukyildirim, Bedri Onur; Gulec, Mehmet Akif (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2018)
Objective: The aim of this study to evaluate the effects of autologous conditioned serum (ACS) on the healing of transected rat Achilles tendons via the assessment of biomechanical and histological parameters. Methods: The study was conducted on 45 male Sprague-Dawley rats. Five rats were used as donors for ACS preparation. Animals were randomly assigned to the experimental or control group. In both groups, the Achilles tendon was cut transversally and then sutured. In the placebo control and ACS-treated groups, saline or ACS, respectively, was injected into the repair zone three times after surgery. Ten rats from each group (ACS group, n = 20; control group, n = 20) were euthanized at days 15 and 30 after surgery for histopathological (n = 5) and biomechanical (n = 5) testing. The histopathological findings were interpreted using the Bonar and Movin scales. Tendon remodelling was evaluated via the immunohistochemical staining of collagen type 3. Biomechanical effects were assessed by tensile testing. Results: The Bonar and Movin scale scores were significantly better in the ACS-treated group on both day 15 (p = 0.003 and p = 0.003, respectively) and day 30 (p = 0.005 and p = 0.004, respectively). The immunohistochemical density of collagen type 3 was significantly lower in the ACS-treated group on day 30 (p = 0.018). The type 1/3 collagen ratios of the groups were similar on days 15 and 30, as determined by Sirius Red staining (p = 0.910 and p = 0.133, respectively). In the biomechanical assessment results, the ACS-treated group's maximum load to failure values were significantly higher on day 15 (p = 0.049). Conclusion: Injection of ACS had a positive effect on the histopathological healing of rat Achilles tendons on days 15 and 30 and on biomechanical healing on day 15. ACS treatment contributed to lowering the collagen type 3 density by day 30. According to our study, ACS may be favourable for the treatment of human Achilles tendon injuries and tendinopathies. (C) 2018 Turkish Association of Orthopaedics and Traumatology. Publishing services by Elsevier B.V.
Keywords: Autologous conditioned serum; Achilles tendon rupture; Rats; Animal model; Growth factors; GROWTH-FACTOR; SURGICAL REPAIR; RUPTURE; Orthopedics